CARD9 Mediates Dectin-2-induced IκBα Kinase Ubiquitination Leading to Activation of NF-κB in Response to Stimulation by the Hyphal Form of Candida albicans - Bi, Liangkuan (American Society for Biochemistry and Molecular Biology, 2010)
The scaffold protein CARD9 plays an essential role in anti-fungus immunity and is implicated in mediating Dectin-1/Syk-induced NF-κB activation in response to Candida albicans infection. However, the molecular mechanism by which CARD9 mediates C. albicans-induced NF-κB activation is not fully characterized. Here we demonstrate that CARD9 is involved in mediating NF-κB activation induced by the hyphal form of C. albicans hyphae (Hyphae) but not by its heat-inactivated unicellular form. Our data show that inhibiting Dectin-2 expression selectively blocked Hyphae-induced NF-κB, whereas inhibiting Dectin-1 mainly suppressed zymosan-induced NF-κB, indicating that Hyphae-induced NF-κB activation is mainly through Dectin-2 and not Dectin-1. Consistently, we find that the hyphae stimulation induces CARD9 association with Bcl10, an adaptor protein that functions downstream of CARD9 and is also involved in C. albicans-induced NF-κB activation. This association is dependent on Dectin-2 but not Dectin-1 following the hyphae stimulation. Finally, we find that although both CARD9 and Syk are required for Hyphae-induced NF-κB activation, they regulate different signaling events in which CARD9 mediates IκBα kinase ubiquitination, whereas Syk regulates IκBα kinase phosphorylation. Together, our data demonstrated that CARD9 is selectively involved in Dectin-2-induced NF-κB activation in response to C. albicans hyphae challenging.